PERAWATAN KECANTIKAN & KEBUGARAN WANITA DI BANJARBARU - Hadaya, Ni’mah; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Current development makes many women have much activity that make them have no time to keep their physical fitness, beside that daily routine would cause boredom which leads into stress if not balanced with recreational activities. The presence of a beauty salon and spa in the middle of town can be one of choice recreational activities for women to get relaxed after their busy activity all day long, so a natural concept would be a great help therapeutic activities for visitors. Biophilic design themes will be applied to create natural feels by trying to ‘bring up’ nature into a building that can improve the space user's well-being in both physiological and psychological by using nature as the main approach.